ERYTHROPOIETIC CELL CULTURES FROM CHICK EMBRYOS - Hagopian, Helen K. (The Rockefeller University Press, 1972)
Erythropoietic cell cultures from very early chick blastoderms survive for several days They show four to seven doublings of the erythroid cells and the appropriate morphological changes from proerythroblasts to mature erythrocytes Cell cycle times are the same as in ovo for the first day of culture, but slow down thereafter The hemoglobins of both the primitive and the definitive red cell series are produced. 5-Bromodeoxyuridine added to the cultures inhibits differentiation and hemoglobin synthesis, though not cell division, but quite soon the cells cease being sensitive The effect of the drug can be reversed by the addition of thymidine.